Association Between Flaming Efficiency and Liquefied Petroleum Gas Pressure and Flaming Time in Hazelnut Sucker Control Done Using a Flame Torch - Ali Tekgüler (Turkish Journal of Agriculture: Food Science and Technology)
Turkish hazelnut (Corylus avellana L.) is naturally grown as a multi-stemmed shrub. This hazelnut produces lots of suckers. Suckers compete with the main branches for nutrients and water. Because the emergence of suckers negatively affects crop management in the hazelnut orchards are required to eliminate at least twice a year. Flaming is an alternative method to chemical and mechanical control methods. In this study, the effect of gas pressure, flaming time on fuel consumption and flaming efficiency in hazelnut sucker control were evaluated. The trials were carried out in an shrub ocak (in Turkish) type hazelnut orchard The results show that the torch flaming method is a useable method for hazelnut basal sucker cleaning. Gas pressure and flaming time had significant effects on fuel consumption and flaming efficiency. 150 s flaming duration and 3 bar pressure is sufficient for the flaming application. Durations above this time will increase fuel consumption and time loss.